Analisis faktor-faktor yang mempengaruhi kesiapan siswa SMP dalam menghadapi ujian nasional berbasis komputer - Trilistiani, Nur Hidayah (Rafandha Press, 2024)
Background: The Computer-Based National Examination (UNBK) is a form of evaluation implemented by the Indonesian government in order to measure the achievement of graduate competencies at certain levels of education. However, the implementation of UNBK also presents its own challenges for students, especially in terms of technological readiness and the ability to adapt to computer-based systems.. Purpose: The purpose of this study was to determine the effect of information technology and communication guidance, motivation, and understanding of computer use on the readiness of 9th grade students to deal with computer-based national examinations in SMP Negeri Se-Kecamatan Pajangan. Method: The type of this research is quantitative research, which is carried out in the Public Middle School in Pajangan Subdistrict, Bantul, DIY. The method of collecting data through a survey with a questionnaire, with a population of 464 and a sample of 210. The analysis technique of the study used a prerequisite test of descriptive analysis, normality, linearity, multicollinearity and multiple linear regression analysis using SPSS 23. Findings: Simultaneous multiple linear regression test results obtained f count of 18,199 greater than f table of 2,65, then between information technology and communication guidance, motivation and understanding of computer use affect the readiness of 9th grade students in dealing with UBNK. Based on the results of this study, the authors suggest several things: (1) The Education Agency should propose that information and communication technology be re-incorporated into the curriculum structure, (2) Teachers are advised to motivate students to be better prepared to face the UNBK, (3) Students are advised to better understand computer usage and matters related to the implementation of UNBK.